The Impact of Hybrid Work System Implementation on Employee Performance in the Digital Era - Sari, Arnanda Putri; Wening, Nur (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines the impact of hybrid work system implementation on employee performance within the framework of the digital era. The acceleration of technological advancements and digital transformation has fundamentally altered the landscape of the workplace, including the domain of human resource management. The hybrid work model, which integrates remote working and on-site office attendance, is widely regarded as a strategic response to the growing demand for flexibility and efficiency in modern organizational settings. A review of numerous empirical studies indicates that the implementation of such a system yields positive outcomes for employee performance, notably through increased temporal and spatial flexibility, enhanced operational efficiency, improved work-life balance, and greater work engagement. Furthermore, hybrid arrangements contribute to higher levels of employee productivity and organizational loyalty by enabling more autonomous work structuring. The successful application of hybrid work systems, however, is highly dependent on the organization’s level of readiness, which includes the availability of robust digital infrastructure, the presence of clear and consistent internal policies, and the practice of communicative and collaborative leadership. However, gaps still remain, particularly in ensuring equal access to digital resources and maintaining consistent employee engagement across remote and on-site teams. Despite its advantages, several implementation challenges persist, such as limited access to adequate support facilities, barriers in team communication, and difficulties in self-managed time allocation. Consequently, the effective deployment of hybrid work systems necessitates a comprehensive and strategic approach, accompanied by strong institutional support across all levels, in order to achieve optimal organizational outcomes.